Bad news for outlaws : the remarkable life of Bass Reeves, deputy U.S. marshall - Nelson, Vaunda Micheaux (Carolrhoda Books, 2009)
This biography profiles the life of Bass Reeves, a former slave who was recruited as a deputy United States Marshal in the area that was to become Oklahoma.